RUPTURA DO TENDÃO CALCÂNEO COMUM EM UM CANINO - Barella, Paola Andressa Das Chagas; Rick, Gabriel Woermann; Bender, Carla Gabriela; Junior, Antônio Maieron; Chitolina, Thalia (Salão do Conhecimento, 2019)
Relatório de caso clínico cirúrgico